Frailty and the homeostatic network - Bandinelli, Stefania; Corsi, Anna Maria; Milaneschi, Yuri; Vazzana, Rosamaria (Acta Biomedica Atenei Parmensis, 2010)
Trajectories of health and functioning with age show extreme variability among different individuals. In frail, older persons the decline in functional reserve is accelerated and compensatory mechanisms start failing, with high risk of homeostasis disruption and consequent negative health outcomes. Frailty is currently conceptualized as an age-related alteration in physiology and pathology that results into a typical constellation of signs and symptoms. Although current attempts to identify frail, older individuals for clinical purposes is based on measures of mobility and motor performance, candidate biological markers that may be specific of the frailty syndrome start to emerge in the literature. Different theories have been drawn to describe the interaction of aging process and loss of ability in performance. One of these hypothesis is based on the progressive dysregulation that occur with age in the homeostatic network and the less efficiency and efficacy in its vital mechanism that allows at all levels integration, from mitochondrial function to societal and community adaptations.